Evaluation of porcine blood meal and plasma bovine plasma, and meat extract as replacement protein sources for dried skim milk in starter swine diets - J A Hansen; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1991)
One-hundred fifty pigs averaging 21 ± 2 d of age were utilized in a 35 d growth assay to determine the efficacy of replacing the dried skim milk portion of a high nutrient-dense diet with four commercially available animal blood or meat co-products. Pigs were blocked by weight and allotted by ancestry and sex to provide six pens (five pigs/pen) per dietary treatment. Diets were randomly assigned within blocks to provide six replicate pens per treatment. The basal diet was formulated using a corn-soybean meal mixture with 20% dried skim milk and 20% dried whey to contain 1.40% lysine, 1.0% calcium, and .90% phosphorus. Spray-dried porcine plasma protein, porcine blood meal, bovine plasma protein, and extracted meat protein were substituted on a lysine basis for dried skim milk; lactose was added to maintain 24.4% lactose. During wk 1, pigs consuming the diet with porcine plasma had 25% and 28% higher daily gain and ADFI, respectively, than those fed the skim milk based diet. There were no differences in growth observed between pigs fed diets containing dried skim milk, porcine blood meal, or bovine plasma. Maximum performance was achieved during the Phase I period by feeding porcine plasma protein. Pigs fed the meat extract diet demonstrated significantly poorer performance than pigs fed the other diets, indicating that it is not an effective replacement for skim milk based on our substitution rates. When pigs were fed a common diet during Phase II, there was a propensity for pigs consuming porcine blood during Phase I to have higher ADFI and ADG, indicating a possible diet interaction between the two phases. During the overall trial (0 to 35 d), differences were detected only between the porcine blood meal and meat extract diets. In conclusion, porcine plasma appeared to offer the potential for greatest performance during Phase I, although there may have been a protein source interaction between Phase I and Phase II diets, indicating that more research is needed to alleviate stall-out during Phase II.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Starter; Performance; DSM; Milk; By-product; BM